2017
DOI: 10.1016/j.cognition.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating processes underlying level-1 visual perspective taking in adults

Abstract: Although reasoning about other people's mental states has typically been thought to require effortful deliberation, evidence from indirect measures suggests that people may implicitly track others' perspectives, spontaneously calculating what they see and know. We used a process-dissociation approach to investigate the unique contributions of automatic and controlled processes to level-1 visual perspective taking in adults. In Experiment 1, imposing time pressure reduced the ability to exert control over one's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
54
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 38 publications
9
54
2
Order By: Relevance
“…More important, however, a PDP re-analysis of Qureshi et al's (2010) data further revealed that performing the secondary task reduced self-perspective detection, but it had no effect on the focal process of avatar-perspective calculation (Qureshi & Monk, 2018), again suggesting that perspective calculation may operate efficiently in L1-VPT. Of most relevance to the current work, Todd et al (2017), using the same L1-VPT task as Qureshi et al (2010), found that imposing time pressure with a response-deadline manipulation-the same one used in the experiments reported here-reduced self-perspective detection but had no effect on avatar-perspective calculation, which once again points to the efficiency of the perspective-calculation process in L1-VPT.…”
Section: The Efficiency Of Perspective Calculationmentioning
confidence: 50%
See 3 more Smart Citations
“…More important, however, a PDP re-analysis of Qureshi et al's (2010) data further revealed that performing the secondary task reduced self-perspective detection, but it had no effect on the focal process of avatar-perspective calculation (Qureshi & Monk, 2018), again suggesting that perspective calculation may operate efficiently in L1-VPT. Of most relevance to the current work, Todd et al (2017), using the same L1-VPT task as Qureshi et al (2010), found that imposing time pressure with a response-deadline manipulation-the same one used in the experiments reported here-reduced self-perspective detection but had no effect on avatar-perspective calculation, which once again points to the efficiency of the perspective-calculation process in L1-VPT.…”
Section: The Efficiency Of Perspective Calculationmentioning
confidence: 50%
“…Indeed, variants of the PDP have been used to estimate processes underlying task behavior in a diversity of content areas, including attitude formation (Hütter, Sweldens, Stahl, Unkelbach, & Klauer, 2012), attributional inference (McCarthy & Skowronski, 2011), decision-making under uncertainty (Ferreira, Garcia-Marques, Sherman, & Sherman, 2006), empathy for pain (Cameron, Spring, & Todd, 2017), moral judgment (Cameron, Payne, Sinnott-Armstrong, Scheffer, & Inzlicht, 2017;Conway & Gawronski, 2013), and racial stereotyping (Krieglmeyer & Sherman, 2012;Payne, 2001). More germane to the current work, the PDP has also been used to elucidate processes underlying altercentric-interference effects in visual perspective taking (Todd, Cameron, & Simpson, 2017).…”
Section: Using Process Dissociation To Isolate Perspective Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…This capacity is akin to that manifested by infants in SRFBTs and is also importantly limited (Surtees and Apperly 2012;Surtees et al 2011Surtees et al , 2016Todd et al 2017; see also Low and Watts 2013;Rakoczy et al 2015, for evidence of important limitations in infants; and Carruthers 2016, pp. 150-151; Rakoczy 2017 for further discussion).…”
mentioning
confidence: 99%